Judgment - Tichy, Noel; Bennis, Warren (Recorded Books, 2007)
Whether we're talking about United States presidents, CEOs, Major League coaches, or wartime generals, leaders are remembered for their best and worst judgment calls. In the face of ambiguity, uncertainty, and conflicting demands, the quality of a leader's judgment determines the fate of the entire organization. That's why judgment is the essence of leadership. Yet despite its importance, judgment has always been a fairly murky concept. The leadership literature has been conspicuously quiet on what, exactly, defines it. Does judgment differ from common sense or gut instinct? Is it a product of luck? Of smarts? Or is there a process for making consistently good calls? Noel Tichy and Warren Bennis have each spent decades studying and teaching leadership and advising top CEOs such as Jack Welch and Howard Schultz. Now, in their first collaboration, they offer a powerful framework for making tough calls when the stakes are high and the right path is far from obvious. They show how to recognize the critical moment before a judgment call, when swift and decisive action is essential, and also how to execute a decision after the call. Tichy and Bennis bring their three-dimensional model to life with interviews with world-class leaders who have thrived or suffered because of their judgment calls.